If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(1/2)*(6*x+4)-((1/3)*(3-(6*x))) = 0
(1/2)*(6*x+4)+(-1/3)*(3-6*x) = 0
1/2*(6*x+4)-1/3*(3-6*x) = 0
1/2*(6*x+4)-1/3*(3-6*x) = 0
5*x+1 = 0
5*x+1 = 0
5*x+1 = 0 // - 1
5*x = -1 // : 5
x = -1/5
x = -1/5
| -1/4w=-9 | | 7=n+3-5n | | 235=60X | | a+x=5a | | 10-4t=-6t | | 63-3=n-5 | | 2(3r-3)=-22+8r | | -8x+3=14 | | -53-9x=35-5x | | 26=x/-5 | | 4j-3=5j | | 5(-7-6n)=-10-5n | | x^2+4x+8=8x+29 | | 2x=.36 | | 5/9(240) | | 3/7+2/5x=1/5x+1 | | 9h+6=10h | | -28=-x+11-(-5) | | -1/5r=-20 | | 5(t+2)=3.2k | | p^2=3p+28 | | (2x+1)*2+(x+1/2)*2=18 | | 5x+10=30whatisx | | 3x-12+2x=13 | | 11.3-72f=-3.82 | | 2k+k=-9 | | 2k=-9k^2-10 | | 11y-7y-10=73.92 | | -x^2y= | | 3+7x-5=4x-12 | | 5p-12-3(p+8)=4 | | f(-3)=-2(3x-2)+x+9 |